Persediaan Barang Dagang Pada Perusahaan Air Minum Mineral di Kota Pontianak - Ra Yadi (Jurnal Ekonomi Integra, 2016)
Variables such as the promotion of research that is focused on aspects of inventory using Economic Order Point (EOQ) to form a quantitative description of the research which is the way in research describing the research object as it is. The data source is taken by way of direct communication through an interview with the company's internal parties. While the data reports and other documentation used to complete the data analysis.The study found that the results of calculations using the EOQ method found an efficient supply that is for the type of mineral water gallons in the amount of 1,217 per booking, and the type of bottles of 1500 ml in the amount of  977 per order, with the frequency of purchases optimum mineral water gallons at 149 times per year, or about 12 times per month and type of bottles of 1500 ml of 112 times per year or a total of nine times per month. Use EOQ method can save the cost of supply of mineral water gallon kinds of Rp 537 575, or 9.58%. Sementra for Pasqua types of bottled mineral water in 1500 ml savings of USD 320 600, or 9.29%.